Experiences and Challenges in Pioneering the Teaching and Learning of Formerly Marginalised Indigenous Languages: The Case of Nambya at the Great Zimbabwe University - Adrian Mafa Phiri (Adonis & Abbey, 2023)
This research article explores the experiences and challenges encountered by pioneer Bachelor of Education Degree students and lecturers of the Nambya language at the Great Zimbabwe University. The introduction of Nambya at the great Zimbabwe University was like navigating uncharted territory since this was the first time ever the language was being offered by any institution of higher learning and more interestingly, the Nambya language was used as the language of instruction. The research adopts qualitative research methods. The data were collected from a sample of graduates who majored in the Nambya language as well as their lecturers. The data were grouped into themes for ease of analysis. The major themes that emerged from the study relate to the availability of literary material, terminology, the language of instruction, lecturer qualification and competence as well as the relevance of modules.